Phonetic Alphabet for Speech Recognition of Czech - Nouza, J.; Psutka, J.; Uhlir, J. (Radioengineering Society, 1997)
In the paper we introduce and discuss an alphabet that has been proposed for phonemicly oriented automatic speech recognition. The alphabet, denoted as a PAC (Phonetic Alphabet for Czech) consists of 48 basic symbols that allow for distinguishing all major events occurring in spoken Czech language. The symbols can be used both for phonetic transcription of Czech texts as well as for labeling recorded speech signals. From practical reasons, the alphabet occurs in two versions; one utilizes Czech native characters and the other employs symbols similar to those used for English in the DARPA and NIST alphabets.
Keywords: speech recognition; phonetic transcription; speech signal labeling